Designing a new type of neutron detector for neutron and gamma-ray discrimination via GEANT4. (April 2016) - Shan, Qing; Chu, Shengnan; Ling, Yongsheng; Cai, Pingkun; Jia, Wenbao
Abstract: Design of a new type of neutron detector, consisting of a fast neutron converter, plastic scintillator, and Cherenkov detector, to discriminate 14-MeV fast neutrons and gamma rays in a pulsed n – γ mixed field and monitor their neutron fluxes is reported in this study. Both neutrons and gamma rays can produce fluorescence in the scintillator when they are incident on the detector. However, only the secondary charged particles of the gamma rays can produce Cherenkov light in the Cherenkov detector. The neutron and gamma-ray fluxes can be calculated by measuring the fluorescence and Cherenkov light. The GEANT4 Monte Carlo simulation toolkit is used to simulate the whole process occurring in the detector, whose optimum parameters are known. Analysis of the simulation results leads to a calculation method of neutron flux. This method is verified by calculating the neutron fluxes using pulsed n – γ mixed fields with different n / γ ratios, and the results show that the relative errors of all calculations are <5%. Highlights: A neutron detector is developed to discriminate 14-MeV fast neutrons and gamma rays. The GEANT4 is used to optimize the parameters of the detector. A calculation method of neutron flux is established through the simulation. Several n/γ mixture fields are simulated to validate of the calculation method.